Rechterlijk Pardon di Indonesia: Integrasi Dimensi Keadilan dan Kemanusiaan Dalam Putusan Hakim - Rahmat Abdullah; Didith Prahara; Ismed A. Gafur (Integralistik, 2026)
Indonesian criminal law has undergone a fundamental paradigmatic transformation from retributive toward restorative justice, notably through the adoption of rechterlijk pardon into the National Criminal Code. Scholarly discourse addressing the integration of this concept into the Indonesian legal framework remains scarce. This study seeks to examine the constitutional and philosophical underpinnings of rechterlijk pardon in Indonesia and to construct a conceptual model for judicial pardon decisions that harmonizes justice and humanity. Employing a normative juridical methodology grounded in secondary data, this research utilizes statutory, conceptual, and comparative approaches. The findings reveal that Article 54 paragraph (2) provisions on rechterlijk pardon are rooted in fundamental constitutional principles and align with the Pancasila philosophical values of divinity, humanity, nationalism, democracy, and justice. This study proposes a conceptual model establishing objective criteria comprising the triviality of the offense, the offender's personal circumstances, conditions surrounding and subsequent to the commission of the criminal act, and considerations of justice and humanity. This research advances Indonesian criminal law scholarship by offering a conceptual framework reconciling legal certainty with substantive justice and furnishing practical guidance for judicial application of Article 54 paragraph (2) of the National Criminal Code.